Alternative Growing Media Under the Same Fertigation Scheme Affected Mineral Accumulation and Physiological Parameters in Grapevine Cultivars - Nikolaos Tzortzakis; Antonios Chrysargyris (Horticulturae)
Under nursery conditions, various organic and inorganic growing media can be used for plant propagation. However, a common fertigation program may have varying effects on plant performance. This study evaluated alternative growing media under the same fertigation scheme in three indigenous Cypriot grapevine cultivars (Xynisteri, Maratheftiko, Giannoudi). Rooted cuttings were grown in pots containing soil, perlite, river sand, peat, and cocosoil. The plants were fertigated with a hydroponic nutrient solution with an electrical conductivity of 2.4 dS/m and a pH of 5.8. Xynisteri grown in peat and cocosoil accumulated minerals such as N and P while showing reduced levels of Na, total phenols, antioxidant capacity, and total flavonoids in the leaves. Additionally, plants exhibited low hydrogen peroxide and malondialdehyde (MDA) content, indicating a non-stressful growing environment. Maratheftiko cultivar accumulated N in perlite, K in cocosoil, and P in peat and cocosoil media. When grown in soil, Maratheftiko showed higher phenol content and increased antioxidant capacity, which is correlated with elevated oxidative stress (higher MDA). Giannoudi appeared to be more adapted to soil and/or cocosoil media, as evidenced by its lower MDA content, total phenols, total flavonoids, and antioxidant activity, compared to plants grown in perlite, sand, and peat. Chlorophyll and total carotenoid levels were increased in Giannoudi grown in soil. In conclusion, both growing media and fertigation practices should be tailored to optimize plant performance under nursery conditions.